„Historia miłosna jak jasna cholera” – wybrane wyobrażenia miłości w liryce polskiej po 1990 roku - Żynis, Bernadetta (Tematy i Konteksty, 2017)
The article presents several scenes of love in erotics generation of “bruLion”. Although these lyrics are very different, they share the conviction of the impossibility of expressing love of affect, lack of new, adequate language, a good story. The lyrics focus on the presentation of almost behavioral symptoms of feeling. They try using irony, shortcut, allusions, distance, banality and hyperboles find the language of contemporary narrative of love. “Love does not know”, and if you do not know, is not able to speak, doomed to live, not to speak (love belonging to the internal order of biology, nature, instinct and passion can not find in the discourse, he did not embrace and will not carry in other words, what is real, when it passes the symbolic does not mean now what it was). However, the analyzed examples show a successful attempt to exceed the “impossibility”, and the record is proof of yet another victory in the words of the inexpressible.